Analysis of Composite Spin Coated Thin Films [Polystyrene and Poly(methyl methacrylate)] - Shanthi1, J.; Priyanga1, J. (Asian Journal of Chemistry, 2013)
Solvent cast composite thin films of polystyrene and poly(methyl methacrylate) have been deposited by spin coating on silica substrate. Thin films of few μm thickness obtained have been examined using UV-visible, photoluminescence, XRD and SEM characterization methods. The band structure of polystyrene tailored by the addition of poly(methyl methacrylate), had 90 % transmittance. The amorphous nature of the material was confirmed using XRD analysis. Homogeneous crack free surface of the coated film has been observed by SEM analysis.